Clonal Analysis of the Quasispecies of Antiviral-Resistant HBV Genomes in Patients with Entecavir Resistance during Rescue Treatment and Successful Treatment of Entecavir Resistance with Tenofovir. Issue 1 (January 2013) - Karatayli, Ersin; Idilman, Ramazan; Karatayli, Senem C; Cevik, Emrah; Yakut, Mustafa; Seven, Gülseren; Kabaçam, Gökhan; Bozdayi, A Mithat; Yurdaydin, Cihan
Background: Clonal analysis of quasispecies of resistant HBV genomes in patients with entecavir (ETV) resistance receiving lamivudine (3TC) plus adefovir (ADV) rescue therapy has never been performed. Methods: A sample of 10 patients with ETV resistance who were switched to 3TC+ADV treatment were analysed for changes in viral quasispecies. Serum samples at baseline, and at months 3 and 6 of 3TC+ADV treatment could be clonally analysed in 7 of 10 patients; 3–82 clones per sample (total 1, 068 clones, mean 63) were sequenced. Results: 3TC+ADV therapy led to a modest decline in HBV DNA. Almost all clones had L180M and M204V 3TC resistance mutations before and during combination therapy. All clones had ≥1 of the S202G, T184F, T184A, T184L, T184I and M250V ETV resistance mutations. The percentages of detected clones bearing 3TC (rtL180M and rtM204V) and ETV mutations did not change with rescue 3TC+ADV therapy. In 7 of 8 patients with detectable HBV DNA (median 5.17 log10 copies/ml) after a median 24 months of ADV therapy, HBV DNA became undetectable with 3TC plus tenofovir after 6 months of treatment. Conclusions: In patients with ETV resistance tenofovir is effective. Clonal analysis data indicate no selection of specific HBV mutants during rescue 3TC+ADV.